Oleic acid-derived oleoylethanolamide: A nutritional science perspective. (July 2017) - Bowen, Kate J.; Kris-Etherton, Penny M.; Shearer, Gregory C.; West, Sheila G.; Reddivari, Lavanya; Jones, Peter J.H.
Abstract: The fatty acid ethanolamide oleoylethanolamide (OEA) is an endogenous lipid mediator derived from the monounsaturated fatty acid, oleic acid. OEA is synthesized from membrane glycerophospholipids and is a high-affinity agonist of the nuclear transcription factor peroxisome proliferator-activated receptor α (PPAR-α). Dietary intake of oleic acid elevates circulating levels of OEA in humans by increasing substrate availability for OEA biosynthesis. Numerous clinical studies demonstrate a beneficial relationship between high-oleic acid diets and body composition, with emerging evidence to suggest OEA may mediate this response through modulation of lipid metabolism and energy intake. OEA exposure has been shown to stimulate fatty acid uptake, lipolysis, and β-oxidation, and also promote food intake control. Future research on high-oleic acid diets and body composition is warranted to confirm these outcomes and elucidate the underlying mechanisms by which oleic acid exerts its biological effects. These findings have significant practical implications, as the oleic acid-derived OEA molecule may be a promising therapeutic agent for weight management and obesity treatment.